Involvement of cholinergic system in suppression of formalin-induced inflammatory pain by cobratoxin - Shi Gao-na; Liu Yan-li; Lin Hai-ming; Yang Shi-lin; Feng Yu-lin; Reid Paul F; Qin Zheng-hong (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the analgesic effect of cobratoxin (CTX), a long-chain α-neurotoxin from Thailand cobra venom, in a rat model of formalin-induced inflammatory pain. Methods: Inflammatory pain was induced in SD rats via injecting 5% formalin (50 μL) into the plantar surface of their right hind paw. CTX and other agents were ip administered before formalin injection. The time that the animals spent for licking the injected paw was counted every 5 min for 1 h. Results: CTX (25, 34, and 45 μg/kg) exhibited a dose-dependent analgesic effect during the phase 1 (0–15 min) and phase 2 (20–60 min) response induced by formalin. Pretreatment with naloxone (0.5 or 2.5 mg/kg) did not block the analgesic effect of CTX. Pretreatment with atropine at 5 mg/kg, but not at 2.5 mg/kg, antagonized the analgesic effect of CTX. Treatment with the nonselective nAChR antagonist mecamylamine (3 mg/kg) inhibited the analgesic effects of CTX in Phase 1 and Phase 2 responses, while with the selective α7-nAChR antagonist methyllycaconitine (3 mg/kg) antagonized the effect of CTX only in the Phase 1 response. Treatment with the α7-nAChR agonist PNU282987 (3 mg/kg) significantly reduced the formalin-induced phase 2 pain response, but only slightly reduced the Phase 1 pain response. Conclusion: The results suggest that CTX exerts an antinociceptive effect in formalin-induced inflammatory pain, which appears to be mediated by mAChR and α7-nAChR.